2006
DOI: 10.1542/peds.2005-0735
|View full text |Cite
|
Sign up to set email alerts
|

Birth Characteristics and Risk of Low Intellectual Performance in Early Adulthood: Are the Associations Confounded by Socioeconomic Factors in Adolescence or Familial Effects?

Abstract: We found that all of the studied dimensions of restricted fetal growth are independently associated with increased risks of low intellectual performance and that these associations are only partly mediated by socioeconomic or familial factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 41 publications
4
35
1
Order By: Relevance
“…Included covariates are listed in the footnotes to the tables and have been described in detail elsewhere. 8 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included covariates are listed in the footnotes to the tables and have been described in detail elsewhere. 8 …”
Section: Methodsmentioning
confidence: 99%
“…8 Briefly, we included information from 4 population-based registries: the Swedish Medical Birth Register, the Swedish Conscript Register, the Multi-Generation Register, and the Population and Housing Census of 1990. Record linkage was possible using the unique National Registration Number that is assigned to each Swedish resident at birth.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several such family-based studies have been conducted for birth weight and cognitive ability. [21][22][23][24][25] In the earliest study, Record et al 21 showed that differences in cognitive ability between nonsiblings aged 11 years in England were greater than those of 2521 sibling pairs and concluded that the association was largely because of confounding by SEP. A study by Lawlor et al 24 also found that, although birth weight was positively associated with cognitive ability at ages 7 to 11 years in a wholecohort analysis, there was no association within 1645 sibling pairs. By contrast, 3 studies have found positive within-sibling associations.…”
mentioning
confidence: 99%
“…3,20,21 Another limitation is that many other factors influence the outcome of infants besides gestational age. 19,[22][23][24][25][26][27][28] Data from the National Institute of Child Health and Development Neonatal Research Network have been used to create an algorithm predicting outcome that considers birth weight, gender, use of prenatal steroids, and singleton pregnancy in addition to estimated gestational age. 19 Each of these factors individually improves outcome for infants by as much as 1 additional week of gestation from 22 through 25 weeks' gestation.…”
Section: Factors To Consider When Counseling Parentsmentioning
confidence: 99%